2008
DOI: 10.1097/aog.0b013e31817e0fcd
|View full text |Cite
|
Sign up to set email alerts
|

Compartment Syndrome With Thrombosis of Common Iliac Artery After Gynecologic Surgery

Abstract: Arterial thrombosis is less common than deep vein thrombosis during gynecologic operations, but the lithotomy position may cause insufficient arterial circulation in both the pelvis and legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Compartment syndrome secondary to thrombosis of the common iliac artery has been described after pelvic surgery performed in the "exaggerated lithotomy position." 11,12 Although providing good exposure for urethral and prostatic surgery, the exaggerated lithotomy position is associated with a low but definite risk of rhabdomyolysis, compartmental syndrome, neurapraxia, and acute renal failure. In the propósito, timely diagnosis of iliac artery thrombosis and restoration of the arterial blood flow prevented the development of compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Compartment syndrome secondary to thrombosis of the common iliac artery has been described after pelvic surgery performed in the "exaggerated lithotomy position." 11,12 Although providing good exposure for urethral and prostatic surgery, the exaggerated lithotomy position is associated with a low but definite risk of rhabdomyolysis, compartmental syndrome, neurapraxia, and acute renal failure. In the propósito, timely diagnosis of iliac artery thrombosis and restoration of the arterial blood flow prevented the development of compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Nakamura et al reported of ALI and compartment syndrome after gynaecological laparoscopic procedure, radical hysterectomy for endometrial cancer. The Authors attributed the ALI occurrence to a prolonged procedural time (lasting for 6 hours) in lithotomy position [ 8 ]. Yeon and collaborators, in 2017 described a really comparable case: external iliac artery thrombosis occurred after laparoscopic radical hysterectomy for cervical cancer, lasting more than 6 hours, and performed in lithotomy position [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the cases of compartment syndrome in gynecologic operation. Nakamura et al [4] reported a case of compartment syndrome due to thrombus of left common iliac artery after prolonged gynecologic surgery with lithotomy position. Cohen and Hurt [5] also described a case of compartment syndrome in gynecologic operation with the intermittent pneumatic compressors of the patient's legs.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen and Hurt [5] also described a case of compartment syndrome in gynecologic operation with the intermittent pneumatic compressors of the patient's legs. Table 1 showed some cases of compartment syndrome in gynecologic operation [45678]. However, compartment syndrome rarely occurs after gynecologic surgery.…”
Section: Discussionmentioning
confidence: 99%